Oviposition by heliothis armigera and H. Punctigera (Lepidoptera: Noctuidae) on okra leaf and smooth-leaf cotton - Hassan, S.T.S.; Wilson, L.T.; Blood, P.R.B. (Entomological Society of America, 1990)
This study compared oviposition by Heliothis armigera (Hübner) and H. Punctigera (Wallengren) on four cotton cultivars: a smooth-leaf cultivar ('Deltapine Smooth Leaf') and a genetically similar hirsute cultivar ('Deltapine 16'), an okra leaf cultivar ('Coker 201 Okra Leaf') and a near-isogenic normal-leaf cultivar ('Coker 201 Normal Leaf'). In the glasshouse, 'Deltapine Smooth Leaf' plants received the lowest number of eggs and 'Coker 201 Normal Leaf' the highest. In the field, 'Deltapine Smooth Leaf' had the fewest eggs and 'Coker 201 Okra Leaf' the most. Both Heliothis species exhibited similar oviposition on different structures on each cultivar for each plant growth stage. Most eggs were laid on mature leaves. In the glasshouse, the lower leaf surface received more eggs than the upper; the upper surface received more eggs in the field. Terminal buds received the fewest eggs in the glasshouse, but in the field, egg numbers on terminal buds, bracts, stems, petioles, and stipules were similar. Analysis of the relative effect of the okra leaf and smooth-leaf traits on oviposition indicates higher oviposition on the okra leaf than on the smooth-leaf plants, although trichome density might in part be responsible for some of the differences.